PERANAN STAF DALAM PENGAMBILAN KEPUTUSAN OLEH PIMPINAN PERGURUAN TINGGI - Arifuddin S (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2008)
In practice, some leaders of higher educational institu-tions have not realized the importance of both academic and admi-nistrative staffs' participation in decision making. It is argued that the staff members of higher education learning play a very important role in decision making process. Their participation would contribute more perspectives to produce good decision. It also encourages creativeness and commitment of staff members. These are crucial factors to improve work motivation of staff members in developing their institution and increasing productivity.